Joint estimation of target time delay and Doppler frequency in passive radar system - ANGPeng W; IUTian-shuang Q; IJing-chun L; ANHai-feng T (Tongxin xuebao)
A novel method of joint estimation of time delay and Doppler shift in passive radar system based on short-time fractional Fourier transform (STFRFT) was proposed.Firstly,the mathematical expression of the STFRFT time-frequency resolution was studied for the quantitative comparison.Secondly,based on the projection envelops of STFRFT,a new method to estimate the time delay and Doppler shift was put forward.Finally,the factors related with the estimation precision such as signal-to-noise ratio (SNR),parameters of Gaussian window were analyzed.The simulation results demonstrate that compared with the CAF based method,proposed method can get precise time delay and Doppler shift estimations with higher probability.